Drivers of Palliative Care and Hospice Use Among Patients With Advanced Lung Cancer - Megan C. Edmonds; Melissa Mazor; Mayuri Jain; Lihua Li; Marsha Augustin; José Morillo; Olivia S. Allen; Amina Avril; Juan P. Wisnivesky; Cardinale B. Smith (Cancer Medicine)
ABSTRACT Purpose Despite rigorous evidence of improved quality of life and longer survival, disparities in the utilization of palliative and hospice care persist for racial and ethnic minority patients with cancer. This study evaluated the impact of psychosocial factors on utilization of these services. Methods Patients with advanced lung cancer were recruited at a large academic urban hospital. Patients were surveyed about their knowledge of palliative care and hospice and their beliefs regarding medical mistrust, lung cancer care, palliative care and hospice. We used univariate and multivariable logistic regression analyses to examine the association between mistrust, knowledge and beliefs among the entire cohort and minority (Black and Hispanic) and non‐minority patients on utilization of palliative care consultation and hospice care use. Results Ninety‐nine of the enrolled participants had a mean age of 64 years. Minority patients were more likely to receive a palliative care referral (p < 0.001) and attend a consult (p = 0.003). Similarly, they were more likely to receive a hospice referral (p = 0.04), however there was no difference in hospice care use based on minority status (p = 0.102). In our adjusted model, older patients and those reporting negative lung cancer beliefs were more likely to receive hospice care (OR: 1.06, 95% CI: 1.004–1.138; OR: 1.04, 95% CI: 1.002–1.093, respectively). Conclusion Minority patients with advanced lung cancer were more likely to receive a palliative care referral and specialty level consultation when compared to non‐minority patients. Our work highlights the importance of proactive referral processes in facilitating access to palliative and hospice services, particularly among younger patients.